2011
DOI: 10.3310/hta15280
|View full text |Cite
|
Sign up to set email alerts
|

A study of the safety and harms of antidepressant drugs for older people: a cohort study using a large primary care database

Abstract: An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per issue and for the rest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 183 publications
(142 reference statements)
8
107
2
Order By: Relevance
“…Thus, a possible explanation for our results and previously observed associations is indication bias, that is, the condition for which the drug was prescribed rather than the drug itself increasing the risk (Coupland et al 2011a). Certain depressive symptoms such as difficulties in concentration, fatigue and insomnia can lead to an increased risk of injury.…”
Section: Possible Mechanismsmentioning
confidence: 52%
“…Thus, a possible explanation for our results and previously observed associations is indication bias, that is, the condition for which the drug was prescribed rather than the drug itself increasing the risk (Coupland et al 2011a). Certain depressive symptoms such as difficulties in concentration, fatigue and insomnia can lead to an increased risk of injury.…”
Section: Possible Mechanismsmentioning
confidence: 52%
“…[62][63][64] Hyponatremia is also associated with SSRI use, primarily in elderly patients with other risk factors for hyponatremia. 65 SSRIs can inhibit platelet aggregation by altering platelet serotonin receptors and modestly increase the risk of gastrointestinal bleeding, but this risk may be doubled with concomitant use of nonsteroidal anti-inflammatory drugs (NSAIDs). 66 Concomitant use of acid-suppressing drugs can significantly reduce the risk of gastrointestinal bleeding.…”
Section: 61mentioning
confidence: 99%
“…(1417, 45, 4758) Several of these studies showed that SSRI users had other risk factors that may be associated with frailty such as multiple comorbidities, higher number of medications(15, 16), baseline higher rate of falls(48), or higher age (i.e. the oldest old).…”
Section: Resultsmentioning
confidence: 99%